Essential and toxic elements in meat of wild birds. Issue 21 (1st November 2016) - Roselli, Carla; Desideri, Donatella; Meli, Maria Assunta; Fagiolino, Ivan; Feduzi, Laura
ABSTRACT: Essential and toxic elements were determined by inductively coupled plasma–atomic emission spectrometry (ICP-AES), mass spectrometry (MS), and atomic absorption (AS) in meat of 14 migratory birds originating from central and northern Europe to provide baseline data regarding game meat consumed in central Italy. In all samples analyzed, cobalt (Co) and chromium (Cr) (total) levels were <0.326 mg/kgww . For nonessential or toxic elements, arsenic (As), barium (Ba), cadmium (Cd), stannous (Sn), thallium (Tl), tellurium (Te), titanium (Ti), cerium (Ce), lantanium (La), and uranium (U) concentrations were <0.326 mg/kgww, thorium (Th) <1.63 mg/kgww, and mercury (Hg) <0.0163 mg/kgww . When detectable, lead (Pb) concentrations always exceeded maximal admissible levels for metal (0.1 mg/kgww ) established by the European Commission for meat. These findings indicate that elevated Pb concentrations in game ingested by humans may be a cause for concern.